Introducing an IP Licence Box in Switzerland: Quantifying the Effects - Florian Chatagny; Marko Köthenbürger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2015)
In response to the increasing international pressure on Switzerland to reform the ring-fenced elements in its tax system, the Swiss Government has put forward a comprehensive tax reform package. The proposal comprises, among other things, the introduction of a licence box, a substantial reduction in the cantonal profit tax rates and an allowance for excess corporate equity. We apply a computable general equilibrium model to quantify the economic effects of this reform. Our results reveal that the licence box, combined with the reduction in the cantonal profit tax, limits the outflow of the tax base of those companies that benefit from the current preferential tax treatment. The reduction in the cantonal profit tax and the fact that regularly taxed companies also benefit from the licence box render the reform package costly, such that the tax revenues will decline after the reform.
Keywords: H25; H32; C68; 330; tax competition; licence box; corporate tax reform; general equilibrium model